The Islamic Perspective of Education of Children With Special Needs: (Case Study at Sada Ibu Inclusion Elementary School) - Fitri Meliani; Nurwadjah Ahmad; Andewi Suhartini (Eduprof : Islamic Education Journal, 2022)
This article aims to provide an Islamic philosophical perspective on disability education by examining some verses of the Qur'an and the Sunnah of the Prophet. This research uses a qualitative approach with a descriptive method. Data collection was carried out by studying verses of the Qur’an and sunnah, documentation, observations and interviews. The locus of this study is SD Inklusi Sada, the capital of Cirebon, with the subject of research of 5 special guidance teachers (GPK) at SD Inklusi Sada, the capital of Cirebon. Data collection will be carried out in April-May 2022. The results showed that inclusion education from an Islamic perspective implemented by the school and teachers at Sada Ibu Inclusion Elementary School was: 1). Giving priority to the needs of ABK; 2). The prohibition of looking contemptly towards ABK; 3). The prohibition against the belief that ABK is a ugliness; 4). Encouraging ABK; and 5). A ban on rebuking ABK. The factors driving the success of inclusive education are: 1). Teacher acceptance; 2). Admission of other students; and 3). Educational methods. Meanwhile, the factors inhibiting inclusive education are: 1). Lack of educational facilities and infrastructure; 2). Lack of professional human resources who understand and are able to handle ABK education; and 3). Lack of knowledge and cooperation of parents of ABK students in educating their children at home. ABSTRAK Artikel ini bertujuan untuk memberikan perspektif filosofis Islam tentang pendidikan disabilitas dengan mengkaji beberapa ayat Al-Qur'an dan Sunnah Nabi. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan dengan mempelajari ayat-ayat Al-Qur’an dan sunnah, dokumentasi, observasi dan wawancara. Lokus penelitian ini adalah SD Inklusi Sada, ibu kota Cirebon, dengan subjek penelitian 5 guru bimbingan khusus (GPK) di SD Inklusi Sada, ibu kota Cirebon. Pengumpulan data akan dilakukan pada April-Mei 2022. Hasil penelitian menunjukkan bahwa pendidikan inklusi dari perspektif Islam yang diterapkan oleh sekolah dan guru-guru di SD SD Sada Ibu Inklusi adalah: 1). Mengutamakan kebutuhan ABK; 2). Larangan memandang menghina ABK; 3). Larangan terhadap keyakinan bahwa ABK adalah keburukan; 4). Mendorong ABK; dan 5). Larangan menegur ABK. Faktor-faktor yang mendorong keberhasilan pendidikan inklusif adalah: 1). Penerimaan guru; 2). Penerimaan siswa lain; dan 3). Metode pendidikan. Sedangkan faktor-faktor yang menghambat pendidikan inklusif adalah: 1). Kurangnya sarana dan prasarana pendidikan; 2). Kurangnya sumber daya manusia yang profesional yang memahami dan mampu menangani pendidikan ABK; dan 3). Kurangnya pengetahuan dan kerjasama orang tua siswa ABK dalam mendidik anaknya di rumah.